(untitled) (Journal of Pathology of Nepal, 2017)
Extracranial meningiomas may be subdivided into primary and secondary types based on absence or presence of intracranial attachments respectively. Primary sinonasal tract meningiomas are rare with unknown etiopathology and non-specific clinical presentation. Of these PEMs only 11.5% are in the nasal cavity and nasal septum. To our knowledge less than 50 cases of PEM of nasal cavity have been reported in the literature. We report a case of a 22 years old male who presented with epistaxis and increasing nasal stuffiness for the last one year.